(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This study examines how sacredness in contemporary mosque prayer spaces is perceived when visual symbolic expressions are no longer the dominant mode of representation. The purpose of this research is to uncover how sacredness within the prayer space of the Al Azhar Summarecon Bekasi Grand Mosque is constructed through the multisensory experiences of worshippers. The novelty of this study lies in the application of a multisensory approach as a methodological framework for investigating mosque sacredness, as well as in its specific examination of the sacred quality of the prayer space at the Al Azhar Summarecon Bekasi Grand Mosque through the sensory experiences of worshippers, an aspect that has not been previously explored in depth. A qualitative method was employed, utilizing in-depth interviews with worshippers as the primary data collection strategy, and the data were analyzed using thematic analysis based on the framework developed by Braun and Clarke. The findings indicate that the sacredness of the prayer space emerges from the integration of multisensory experiences involving auditory, visual, tactile, olfactory, and kinesthetic perceptions. Auditory experiences, particularly the imam’s recitation, the call to prayer, and the sound of water, play a dominant role in nurturing devotion and spiritual engagement. Natural elements function as mediators of sacredness, while bodily comfort constitutes a fundamental condition for maintaining spiritual focus during worship. Visual elements operate as a controlled spatial background that supports worship activities without dominating perceptual attention. These findings demonstrate that sacredness in contemporary mosque prayer spaces is not primarily visual in nature, but is holistically embodied through an integrated multisensory experience.